2014
DOI: 10.7567/jjap.54.01ag07
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of growth rate of plants by bubble discharge in water

Abstract: The effect of bubble discharge in water on the growth rate of plants was investigated experimentally for application to plant cultivation systems. Spinach (Spinacia oleracea), radish (Raphanus sativus var. sativus), and strawberry (Fragaria × ananassa) were used as specimens to clarify the effect of the discharge treatment on edible parts of the plants. The specimens were cultivated in pots filled with artificial soil, which included chicken manure charcoal. Distilled water was sprayed on the artificial soil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…14- 18 Volin et al 19 achieved either delayed or accelerated germination in several different agricultural species without signicantly affecting the percentage of germination. For an example, using a selective gas and plasma conditions, germination was delayed in pea, radish, soybean, corn and bean seed, while the germination was accelerated in soybean and corn seed.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation
“…14- 18 Volin et al 19 achieved either delayed or accelerated germination in several different agricultural species without signicantly affecting the percentage of germination. For an example, using a selective gas and plasma conditions, germination was delayed in pea, radish, soybean, corn and bean seed, while the germination was accelerated in soybean and corn seed.…”
Section: 10mentioning
confidence: 99%
“…17,23 The low pH and elevated concentration of H 2 O 2 notably affect the seed germination and plant growth. 24 Takahata et al 18 investigated the effect of bubble (one tube) discharge in drained water on plant growth as well as edible parts of the plant. Authors reported that the plants watered with plasma treated water have shown faster growth and the fruits contain higher sugar.…”
mentioning
confidence: 99%
“…In the last few years, studies have been conducted on selected species to test the effect of PAW on seed germination and plant growth …”
Section: Introductionmentioning
confidence: 99%
“…16,17) Various electrode configurations are employed for APPJs such as capillary dielectric barrier discharge, 18,19) microhollow cathode discharge, 20) and microfluidic discharge. [21][22][23] Among these configurations, the capillary helium (He) discharge configuration with an external electrode(s) has been widely utilized in biology-related research.…”
Section: Introductionmentioning
confidence: 99%